Analysis of dependability and sustainability requirements to support the deployment of dense data center architectures - VALE, Kádna Maria Alves Camboim (2020)
VALE, Kádna Maria Alves Camboim também é conhecida em citações bibliográficas por: CAMBOIM, Kádna Maria Alves